Utilizing Cash Waqf Through Multipurpose Micro Financing at the Mutiara Tarbiyah Waqf Institution - Fikri, Fikri; Noor Sayuti, Muhammad; Zulkifli, Zulkifli; Muzalifah, Muzalifah (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2024)
The aim of this research is to determine the mechanism and impact of utilizing cash waqf through multipurpose micro financing carried out by the Mutiara Tarbiyah Waqf Institution. The method uses qualitative research. The approach taken is qualitative and descriptive. Data collection through observation, interviews, documentation. There are several stages in data analysis carried out by researchers, namely, data reduction, data presentation and conclusions. The results of this research are a multipurpose micro financing mechanism through cash waqf carried out by the Mutiara Tarbiyah Waqf Institution through several stages and the conditions for being able to take the financing program are teachers/employees at Sahabat Alam School. The first stage, teachers/employees submit the items they want. Second, Nazir will calculate how much fees will be paid. Third, sign a murabahah agreement. Fourth, Nazir purchases goods. The five teachers/employees are waiting for the goods to arrive and finally the monthly installment payment. This financing has a positive impact in the form of strengthening teacher/employee capacity, flexible access to funds in improving teacher/employee welfare, institutional operational support, assistance for school activities. The challenge faced is how to maintain waqf financial liquidity so that it remains maintained, stable and minimizes the occurrence of non-performing loans (NPL). One approach that can be taken is to apply 5C. Even though they haven't implemented 5C, they can minimize this by providing a salary cut.